The application of the plea-bargaining legal frameworks in Malaysia and England & Wales / Ahmad Ridhwan Abd Rani - Abd Rani, Ahmad Ridhwan (2020)
The plea-bargaining process is created to provide for speedy disposition of cases in criminal courts. Criminal cases which are deemed by the courts to be minor would be filtered out, which inevitably would save the courts' time and effort. The experiences from many jurisdictions have showed that unregulated plea-bargaining process would lead to procedural abuse by some criminal justice actors, particularly the prosecutors. Malaysia has introduced new and formal plea-bargaining procedures in Sections 172C and 172D of the Criminal Procedure Code. However, in the application of the plea bargaining legislation, the criminal justice actors face several constraints involving legal, technical, and operational ones. Previous local researches has not addressed the application of the plea-bargaining law, let alone the impediments in such process. Given such impediments, the central thesis is twofold. Firstly, the criminal justice actors in the plea-bargaining process are somewhat reluctant to follow the new provisions in the Criminal Procedure Code which changes the plea-bargaining procedures. Secondly, the rationales for their unwillingness to follow the new law are due to the legal, operational and technical impediment. Guided by these prepositions, the research aims at examining the application of the new plea-bargaining procedural provisions under the Criminal Procedure Code and the impediments facing the criminal justice actors. At the theoretical level, this research analyses how the trial shadow theory, the rational choice theory, and the functional-system theory would inform the implementation of the plea bargaining process. This study adopts qualitative methodology, in which the primary data is obtained from semi-structured interviews from fifteen respondents involving the prosecutors, defence counsels, judges, and accused persons. The sampling technique used is purposive sampling. The primary data is triangulated with the representative from the Malaysian Bar Council. The findings of this research are in Chapter Five. The legal analyses of England and Wales as well as Malaysia are presented in Chapter Three and Chapter Four respectively. The research reveals that the formal plea-bargaining process is deemed unfavourable due to the legal, technical, and organisational impediments. This study is aimed at contributing to the body of knowledge and literature on the plea-bargaining process in Malaysia, which would assist policy makers and other actors who are directly involved in such process.